Evaluation of the novel TSPO radiotracer [18F] VUIIS1008 in a preclinical model of cerebral ischemia in rats. Issue 1 (December 2017) - Pulagam, Krishna; Colás, Lorena; Padro, Daniel; Plaza-García, Sandra; Gómez-Vallejo, Vanessa; Higuchi, Makoto; Llop, Jordi; Martín, Abraham
Abstract Background In vivo positron-emission tomography (PET) imaging of transporter protein (TSPO) expression is an attractive and indispensable tool for the diagnosis and therapy evaluation of neuroinflammation after cerebral ischemia. Despite several radiotracers have shown an excellent capacity to image neuroinflammation, novel radiotracers such as [18 F] VUIIS1008 have shown promising properties to visualize and quantify the in vivo expression of TSPO. Methods Longitudinal in vivo magnetic resonance (MRI) and PET imaging studies with the novel TSPO radiotracer 2-(5, 7-diethyl-2-(4-(2-[18 F] fluoroethoxy) phenyl) pyrazolo [1, 5-a] pyrimidin-3-yl)-N, N-diethylacetamide ([18 F] VUIIS1008), and (N, N-diethyl-2-(2-[4-(2-fluoroethoxy)-phenyl]-5, 7-dimethyl-pyrazolo [1, 5-a] yrimidin-3-yl)-acetamide ([18 F] DPA-714) were carried out before and at days 1, 3, 7, 14, 21, and 28 following the transient middle cerebral artery occlusion (MCAO) in rats. Results MRI images showed the extension and evolution of the brain infarction after ischemic stroke in rats. PET imaging with [18 F] VUIIS1008 and [18 F] DPA714 showed a progressive increase in the ischemic brain hemisphere during the first week, peaking at day 7 and followed by a decline from days 14 to 28 after cerebral ischemia. [18 F] DPA714 uptake showed a mild uptake increase compared to [18 F] VUIIS1008 in TSPO-rich ischemic brain regions. In vivo [18 F] VUIIS1008 binding displacement with VUIIS1008 was more efficient than DPA714. Finally, immunohistochemistry confirmed a high expression of TSPO in microglial cells at day 7 after the MCAO in rats. Conclusions Altogether, these results suggest that [18 F] VUIIS1008 could become a valuable tool for the diagnosis and treatment evaluation of neuroinflammation following ischemic stroke.